Upaya Membentuk Karakter Religius Siswa Melalui Layanan Bimbingan dan Konseling Terintegrasi di Sekolah Dasar - Hasrul, Hasrul (Universitas Mathla'ul Anwar Banten, 2025)
This article aims to provide a descriptive explanation of the efforts made by researchers to shape the religious character of students through integrated guidance and counseling services in elementary schools over the past five years. The method used is a literature study following a five-step process. These findings describe that in the past five years or from 2019 to 2024, the implementation of integrated guidance and counseling services for the formation of the religious character of elementary school students in Indonesia is still very minimal. This is evident in the small number of articles published in scientific journals. Efforts to shape the religious character of elementary school students can be carried out through three strategies for integrative guidance and counseling services, namely: specific strategies, teacher collaboration strategies, and family empowerment strategies.